From invention to industry from a social movement perspective: The emergence of the 3D printing industry - Christian Lechner; Abeer Pervaiz (Journal of Innovation and Entrepreneurship, 2020)
In the entrepreneurship literature, the phenomenon of industry emergence has been largely investigated from an institutional perspective. Appropriate institutions would allow then a group of individual entrepreneurs ("the heroes") to create an industry through innovative ventures. New ventures create new industries and firm entry, survival, and exit drive industry evolution. Our research, however, explores what creates the favorable set of circumstances for new ventures to emerge and focuses on the pre-emergence phase and we propose that the patterns of emergence resemble those of social movements. Through an actor perspective, this research highlights the existence of diverse actors, not necessarily entrepreneurs, who are necessary to trigger a collective action during the pre-emergence phase of industries. This research is also distinct from entrepreneurial ecosystems as its development already requires some successful entrepreneurial action. The 3D printing industry was chosen as a single longitudinal case study, where the actors are the embedded units of analysis. The findings of the study lead to the identification of three aggregate dimensions-"Social Movement Composition," Temporal Engagement," and "Coalitions Development"-that were prevalent during the pre-emergence phase of the 3D printing industry. Our propositions emphasize the importance of large collective action and the role of multiple actors in order to create the conditions for, first, firm emergence and, the second, to the process of industry emergence.
Keywords: 650; Industry emergence; Social movements; Entrepreneurship; 3D printing industry